Educación y comunicación en el Eutidemo de Platón - Pascual LC, Fernando (Alpha Omega, 2010)
The Euthydemus offers important elements of Platonic thought, from which emerges the need to study philosophy in order to achieve a good life. This article offers a brief introduction to this work of Plato. It then presents an analysis of several ideas that appear throughout the discussion, putting special emphasis on those dealing, directly or indirectly, with the main theme of the Dialogue (Education and Human Communication). It concludes with a synthesis of the arguments given in the work.